Engineer Millet School - pioneer in Tamandaré, Pernambuco, Brazil / Escola Engenheiro Millet – pioneira em Tamandaré, Pernambuco, Brasil - Maria do Carmo Ferrão Santos (Diversitas Journal, 2019)
The text aims to gather information about the first municipal school of Tamandaré, inaugurated in 1928, so that the history of this extraordinary legacy be divulged for generations. This patrimony of immense social importance worked for four decades, at a time when almost the entire population was illiterate. It also contemplates a brief biography about the engineer Millet, since it had its name chosen to nominate the first great social work built in Tamandaré.